An fMRI Study of Response and Semantic Conflict in the Stroop Task - Parris, Benjamin A.; Wadsley, Michael G.; Hasshim, Nabil; Benattayallah, Abdelmalek; Augustinova, Maria; Ferrand, Ludovic (Frontiers in Psychology, 2019)
An enduring question in selective attention research is whether we can successfully ignore an irrelevant stimulus and at what point in the stream of processing we are able to select the appropriate source of information. Using methods informed by recent research on the varieties of conflict in the Stroop task the present study provides evidence for specialised functions of regions of the frontoparietal network in processing response and semantic conflict during Stroop task performance. Specifically, together with previous research our data indicate that the left inferior PFC plays an role in the processing of both response and semantic (or stimulus) conflict, whilst regions of the left parietal cortex (BA40) play an accompanying role in response, but not semantic, conflict processing. Moreover, our study reports a role for the right mediodorsal thalamus in processing semantic, but not response, conflict. In none of our comparisons did we observe activity in the anterior cingulate cortex, a finding we ascribe to the use of blocked trial type presentation and one that has implications for theories of ACC function.